2012
DOI: 10.4236/ajmb.2012.22015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of fruit specific promoter from <i>Cucumis sativus</i> L.

Abstract: The isolation and characterization of fruit specific promoters are critical for the manipulation of nutritional value and agronomic quality of fruits by genetic engineering and also opened a new era in edible vaccine technology. Expansins are proteins that induce loosening of individual plant cells by disrupting the non-covalent interactions between cellulose and hemicellulose microfibrils and hence have role in growth programs including fruit ripening. We report the identification of an expansin gene (CsExp) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Studies have indicated that the G-box elements cannot act alone and require additional CREs for their function 63 , 64 . This statement supports the fact that the promoter region of cucumber PRGs contains a number of CREs required for the high and specific expression of the gene in fruit tissues 65 . Our study found that the G-box was located in CsDELLA, CsFIE, CsMET1, CsARF19, CsPYR1, CsCKX2, CsAGL6, CsTPL and CsGAST1 .…”
Section: Discussionsupporting
confidence: 75%
“…Studies have indicated that the G-box elements cannot act alone and require additional CREs for their function 63 , 64 . This statement supports the fact that the promoter region of cucumber PRGs contains a number of CREs required for the high and specific expression of the gene in fruit tissues 65 . Our study found that the G-box was located in CsDELLA, CsFIE, CsMET1, CsARF19, CsPYR1, CsCKX2, CsAGL6, CsTPL and CsGAST1 .…”
Section: Discussionsupporting
confidence: 75%